GC-MS Analysis of Chemical Composition of the Essential Oil of Salvia officinalis from Iran - Soleymani, Esmaayel; Hadi Meshkatalsadat, Mohammad (Asian Journal of Chemistry, 2010)
The water-distilled essential oil produced from the aerial parts of Salvia officinalis, endemic in Iran, was analyzed by GC/MS. Thirty one compounds were identified representing 62.19 % of the total components detected with b-eudesmol (11.1 %), camphene (10.1 %) and trans-b- ocimene (9.4 %) as the major constituents.